2014
DOI: 10.7763/ijeeee.2014.v4.302
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Churn Prediction Model in Mobile Telecommunication Industry

Abstract: In most industries where switching costs are prevalent, the landscape of activities is painted of Customers attrition or churn (Clients who want to switch or change their suppliers for various reasons). This phenomenon is ubiquitous in the telecommunication industry and every aspect related to it, leads to believe that it's steeply growing. As the market is fiercely competitive, and the number of prepaid customers is increasing, it is vital that companies proactively tackle the defection of their customers by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Using customer demographics (age and gender) as churn predictors in the churn prediction model is common in the literature [6,7,25,[29][30][31][32][33][34][35][36] found that young people below forty-five years of age are more likely to churn. The similar results were found by [33,36]: customers between forty-five and forty-eight years old are more likely to churn.…”
Section: New Customer Churn Model Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using customer demographics (age and gender) as churn predictors in the churn prediction model is common in the literature [6,7,25,[29][30][31][32][33][34][35][36] found that young people below forty-five years of age are more likely to churn. The similar results were found by [33,36]: customers between forty-five and forty-eight years old are more likely to churn.…”
Section: New Customer Churn Model Variablesmentioning
confidence: 99%
“…They used customer information, such as age, sex and call details. Numerous studies recognised the importance of including customer complaints as an attribute in their churn prediction model [6,7,25,31,32,34,35,39,41,43,45,46,50].…”
Section: Used Influence Maximisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic Regression (LR) for classification, and Voted Perceptron (VP) for estimation has been used in the model. According to the results obtained, the predictive power of the hybrid model has been reported to be better than of individual methods (Olle 2014).…”
Section: Studies Of Churn Analysis In Telecommunication Industrymentioning
confidence: 97%
“…The cost of acquiring new customers is 5 to 10 times higher than the cost of retaining existing customers [26], and the churn rate of new customers is often higher than existing customers [27]. For telco operators, the adoption of a retention strategy can obtain greater profits by regaining trust from customers who have already enjoyed their services and products.…”
Section: Research Motivation and Contributionsmentioning
confidence: 99%